Decoupling between growth rate and storage remobilization in broadleaf temperate tree species. (30th March 2020) - Piper, Frida I.
Abstract: Temperate trees rely on carbon (C) and nutrient remobilization from storage to resume growth after winter. Minimum storage levels during the growing season suggest that remobilization could signify that C availability is insufficient to meet growth demands; consequently, growth might be C and/or nutrient limited. However, it remains unclear whether higher growth demands are covered by higher remobilization. This study examined whether higher C and nutrient demands associated with fast growth or deciduousness rely on greater remobilization. In 11 sympatric deciduous and evergreen angiosperm tree species from southern South America, the magnitude of seasonal remobilization of C and nutrient storage was assessed as the seasonal minimums (relative to seasonal maximums) of whole‐tree non‐structural carbohydrates (NSCs), nitrogen (N) and phosphorus (P) concentrations and pools. The basal area increment and stem wood density were determined for each tree, from which the biomass radial increment (BRI) was estimated. The effects of leaf habit and BRI on the seasonal minimum NSC and nutrient concentrations and pools were analysed using linear mixed effects models. Radial growth was not related to seasonal minimum NSC or nutrient concentrations and pools in either the evergreens or deciduous angiosperms; thus, faster growth was not associated with greater remobilization of C or nutrient stores. Furthermore, larger trees grew faster than smaller ones, but did not have higher remobilization. Deciduous species had higher year‐round whole‐tree NSC and nutrient concentrations than evergreens; however, both groups had similar BRI and seasonal minimum concentrations and pools of NSCs and nutrients. Neither growth rate nor leaf habit drove the magnitude of C and nutrient remobilization in the angiosperm trees examined here, indicating no C or nutrient limitation. This result contradicts the view that growth and storage strongly regulate one another, as proposed by a growth‐storage trade‐off. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.